Intervensi Promosi Kesehatan Melalui Edukasi Gizi Oleh Kader Desa Dalam Pencegahan Stunting - Raihana Alkaff; Yuli Amran; Milza Nasrul Rosad; Nurmeilis Nurmeilis (FKM UIN Sumatera Utara Medan, 2022)
The Indonesian government makes stunting one of the priority health problems that must be addressed seriously and in 2017 set 100 priority districts for stunting prevention. From October to December 2019, Syarif Hidayatullah State Islamic University (UIN) Jakarta held a health promotion intervention program through nutrition education for pregnant women, breastfeeding mothers and mothers of toddlers in Gianyar Regency, Bali. The results of the evaluation of the intervention program by the UIN Syarif Hidayatullah Jakarta team showed a significant increase in the knowledge of 65.8% of pregnant women, breastfeeding mothers and mothers of toddlers in 6 villages in Gianyar Regency. However, the increase in knowledge scores was still around 12.33 points from the initial score of 62.28. This shows that there is still a need for special attention to efforts to increase public knowledge about stunting prevention through effective behavior change communication.Optimizing the role of “Leadership” in stunting prevention management programs at the village/sub-district level is very necessary in ensuring the suitability of stunting prevention programs such as the transfer of information (relay) related to stunting prevention programs that have been carried out at the time of the change of leadership. In addition, communication skills to change behavior and use of health promotion media tools in stunting prevention are needed as basic materials to support optimizing the role of cadres in providing counseling in supporting the role of midwives/health centers in the community